Sosialisasi Sadari Pada Remaja Putri di Desa Pulo Peding Kecamatan Babussalam Kabupaten Aceh Tenggara - Yessy Syahradesi Br Tambunan; Fika Lestari; Purnama Sari Cane (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Adolescence is a transition period from children to adults. Adolescence lasts from the age of 15-20 years. Developmental changes that occur during adolescence include physical, psychological and psychosocial development (Gainau, 2021). Adolescent girls experience secondary sexual signs in the form of widening of the hips, breast growth, hair growth around the genitals and armpits, as well as growth of the uterus and vagina (Sarwono, 2016). Breast self-examination or what is known as BSE, is a form of early detection prevention effort whose implementation procedure can be carried out by each individual woman more easily in order to find symptoms or signs related to breast cancer, for example; lump in the breast (Sari P, Sayuti S, Ridwan M, Rekiaddin LO, 2020). This community service activity takes the form of outreach about breast self-examination (BSE) to young women in Pulo Peding village, Babussalam District, Southeast Aceh Regency. This activity was attended by 30 participants with the aim of increasing teenagers' knowledge about BSE. The results of this activity were an increase in teenagers' knowledge before and after being given socialization, namely from an average knowledge score of 50 to 80. It is hoped that this activity can be useful for young women and doing BSE regularly to detect breast cancer early.